PRE-SERVICE ENGLISH TEACHERS’ PERSPECTIVES TOWARDS TEACHER PROFESSIONALISM: A NARRATIVE INQUIRY - Diputro, Angga Dwi Cahyo Andar; Suwarso, Pratnyawati Nuridi (Universitas Pendidikan Indonesia, 2020)
Since 2018, there are 2.449 pre-service teachers (PSTs) prepared to be professional teachers. In Indonesia, those PSTs are enrolled in the professional development program called PPG. To become a teacher, they have to obey teacher professionalism regulated in the Law Number 14 Year 2005 explaining, among others, that teacher roles, teacher competencies, and teacher professional development programs are the important aspects in determining teacher professionalism. This research aims to know their perspectives towards teacher professionalism. The method used was the qualitative research method and a narrative inquiry research design. The subjects were ten pre-service English teachers who have different background of studies, experiences, and even interests in becoming teachers. An adapted semi-structured interview guideline from Yuwono (2008) and FGD guideline developed from 4 previous studies and the Law Number 14 Year 2005 were employed to collect the data. To avoid bias data, triangulation of source and methodology was conducted. The results show that the PSTs thought that it has to be more flexible and practical. They also revealed that teacher roles, teacher competencies and teacher professional development program are the determiners of teacher professionalism as what is explained in the law. However, they considered that teacher roles can be supportive aspect towards teacher competencies performed in the classroom. Thus, teacher competencies are the most dominant factor that can influence and determine teacher professionalism. Further, professional teacher certification consisting various professional development programs is needed to improve their competencies.Â